Transcellular Transport of Heparin-coated Magnetic Iron Oxide Nanoparticles (Hep-MION) Under the Influence of an Applied Magnetic Field - Kyoung Ah Min; Faquan Yu; Victor C. Yang; Xinyuan Zhang; Gus R. Rosania (MDPI AG, 2010)
In this study, magnetic iron oxide nanoparticles coated with heparin (Hep-MION) were synthesized and the transcellular transport of the nanoparticles across epithelial cell monolayers on porous polyester membranes was investigated. An externally applied magnetic field facilitated the transport of the Hep-MION across cell monolayers. However, high Hep-MION concentrations led to an increased aggregation of nanoparticles on the cell monolayer after application of the magnetic field. Our results indicate that magnetic guidance of Hep-MION most effectively promotes transcellular transport under conditions that minimize formation of magnetically-induced nanoparticle aggregates. Across cell monolayers, the magnet's attraction led to the greatest increase in mass transport rate in dilute dispersions and in high serum concentrations, suggesting that magnetic guidance may be useful for in vivo targeting of Hep-MION.